Evaluation of factors affecting alveolar ridge height and facial bone thickness in Chinese maxillary central incisors by cone beam CT - Duoling Xu; Chengjie Xie; Huimin Yu; Zhiyong Zhang; Junfa Zheng; Shulan Xu (Elsevier, 2021)
Background/purpose: In the immediate implantation of maxillary central incisors, the height of the alveolar bone is lost, and there is often a risk of bone fracture due to the thin buccal bone wall (BBW). The purpose of this study was to assess the effects of smoking, age, and root position in the alveolar bone on the BBW and the distance between the cemento-enamel junction (CEJ) and the facial bone crest (FBC) of Chinese maxillary central incisors. Materials and methods: The patients were divided by smoking, gender, age, and root sagittal position in the alveolar bone. BBW thickness was measured at the following sites: the 4 mm apical to the CEJ, the middle of the root, and the apex. The distance from the CEJ to the FBC was also evaluated. Results: Cone beam CT (CBCT) data for the maxillary central incisors of 645 patients (323 males and 322 females) were selected and analyzed. The CEJ-FBC distance in patients who smoked (2.79 ± 0.78 mm) was significantly greater than that of non-smokers (2.54 ± 0.69 mm). The BBW in subtype III (0.74 ± 0.43 mm, 0.81 ± 0.36 mm) was thinner than that in subtypes I and II at 4 mm apical to the CEJ and in the middle of the root, with a statistically significant difference (p < 0.05). Conclusion: In most Chinese people, smoking, gender, age, and the position of the root in alveolar bone are all important factors that must be considered before immediate implantation is undertaken.